Законодавчі обмеження права громадян на захист у кримінальному процесі: проблемні питання - Карпова, Н.Ю. (Часопис Київського університету права, 2009)
В данной статье рассматривается вопрос обеспечения права каждого на защиту от криминального преследования. Исследуются такие понятия как право на адвоката задержанного, подозреваемого или обвиняемого с момента лишения воли, право свидетеля быть представленным адвокатом. Главное внимание уделяется праву иметь адвоката во время допроса. Основная идея статьи касается таких вопросов, как право каждого на правовую помощь, обеспечение права каждого на защиту от криминального преследования, допуск защитника к защищаемому. Ключевые слова: право каждого на правовую помощь, обеспечение права каждого на защиту от криминального преследования, допуск защитника к защищаемому. The published article is determined for studying such a question as right of everyone to counsel. The suggested article includes observing such a question as assertion of a right of everyone to be defended from criminal prosecution. The article produces such notions as the right to counsel from the time that an apprehended, a suspected or an accused is taken into the custody, right of a witness to be represented by counsel. The main attention is given to right to have legal counsel present during interrogation. The key note concerns such issues as right of everyone to counsel, assertion of a right of everyone to be defended from criminal prosecution, the defender’s access to the defended person. Key words: right of everyone to counsel, assertion of a right of everyone to be defended from criminal prosecution, the defender’s access to the defended person.